2002
DOI: 10.1111/j.1530-0277.2002.tb02598.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Alcoholic Liver Disease–Recent Advances

Abstract: The article summarizes the proceedings of a symposium on recent advances in research on the pathogenesis of alcoholic liver disease at the 2001 RSA meeting in Montreal, Canada. The chairs were Amin A. Nanji and Samuel W. French. The presentations were (1) Role of inflammatory mediators in alcoholic liver injury by Amin A. Nanji, (2) Role of endotoxin, lipopolysaccharide binding protein, CD14 and Toll receptors in alcoholic liver injury by Grace Su, (3) Fatty acid ethyl esters: toxicity, metabolism and markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…It is becoming increasingly evident that alcohol enhances hepatic apoptosis in humans and in animal models of liver disease and when added to cultured hepatocytes. [15][16][17][18]20 Indeed, we showed significant increases in caspase-3 activity in hepatocytes and sinusoidal endothelial cells isolated from rats chronically fed alcohol for 14 weeks. 19,20 Also, we demonstrated that a pancaspase inhibitor can attenuate liver injury and apoptosis in alcohol-fed rats injected with lipopolysaccharide.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It is becoming increasingly evident that alcohol enhances hepatic apoptosis in humans and in animal models of liver disease and when added to cultured hepatocytes. [15][16][17][18]20 Indeed, we showed significant increases in caspase-3 activity in hepatocytes and sinusoidal endothelial cells isolated from rats chronically fed alcohol for 14 weeks. 19,20 Also, we demonstrated that a pancaspase inhibitor can attenuate liver injury and apoptosis in alcohol-fed rats injected with lipopolysaccharide.…”
Section: Discussionmentioning
confidence: 69%
“…Apoptosis is increasingly recognized as a major mechanism for cell death in many forms of liver disease, including both experimental models of alcohol-related injury and human alcoholic liver disease. 9,[15][16][17][18][19][20] Recent studies suggest that apoptosis may lead to hepatic neutrophil infiltration (reviewed in Jaeschke et al 11 ). This seems somewhat paradoxical in that apoptosis is normally thought to lead to orderly, noninflammatory removal of dead cells.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the female liver is more vulnerable to alcoholic injury than the male liver 41) , and such interactions may be attributable to greater vulnerability in female A227 carriers. In contrast, HDL-C levels showed no significant difference between the PPARA-V227A and PPARA-WT.…”
Section: Discussionmentioning
confidence: 99%
“…The paraffin sections were cut on glass slides and stained with eosin for histopathological examination. The sections were examined under a light microscope to detect any damage to the tissue with 500 Â magnification (Nanji et al, 2002).…”
Section: Histopathological Studiesmentioning
confidence: 99%